Implementing Augmented Reality in Inclusive Education: Experiments and Potential - Erni Murniarti; Hadi Prayitno; Guntur Arie Wibowo; Suparmi; Elfi Yuliani Rochmah (GoAcademica Research & Publishing, 2023)
Technological developments often support the development of learning methods, where currently the implementation of e-learning is quite common. Do not miss inclusive school Students can be helped in their education through the use of this technology, namely the use of Augmented Reality. This study aims to look at the implementation and potential that can be provided by the presence of Augmented Reality for inclusive education. This research was conducted using a descriptive qualitative approach. The data used in this study were obtained from the library study method. The results of this study then found that Augmented Reality cannot be implemented in general as a learning medium in schools like other e-learning media. However, the use of Augmented Reality can help educators to provide knowledge for students. In the case of inclusive education, generally, the presence of Augmented Reality has a positive impact and is liked by students. This shows that the existence of Augmented Reality can be useful as a learning medium for inclusive education.